Thrombolytic and Cytotoxic Activities of Terminalia bellerica Roxb. (Bangladesh Pharmaceutical Journal, 2015)
The present study was designed to investigate the thrombolytic activity and cytotoxic potential of the methanolic extract of bark of Terminalia bellerica Roxb. The cytotoxicity was assessed with the brine shrimp lethality bioassay and thrombolytic effect with human blood. The brine shrimp lethality bioassay was used to evaluate cytotoxicity (LC50 = 3.21 ?g/ml) compared to vincristine of sulphate (LC50 = 0.512 ?g /ml). It was also evaluated as thrombolytic agent as compared to streptokinase. It has significant thrombolytic activity (32.95%) compared to standard streptokinase (70%). DOI: http://dx.doi.org/10.3329/bpj.v16i2.22293 Bangladesh Pharmaceutical Journal 16(2): 131-135, 2013